Thoracic gas compression during forced expiration in patients with emphysema, interstitial lung disease and obesity - Piirilä, Päivi L; Hodgson, Ulla; Wuorimaa, Tomi; Smith, Hans-Jürgen; Sovijärvi, Anssi RA (BMC pulmonary medicine, 2014)
Background Dynamic gas compression during forced expiration has an influence on conventional flow-volume spirometry results. The extent of gas compression in different pulmonary disorders remains obscure. Utilizing a flow plethysmograph we determined the difference between thoracic and mouth flows during forced expiration as an indication of thoracic gas compression in subjects with different pulmonary diseases characterized by limitations in pulmonary mechanics. Methods Patients with emphysema (N = 16), interstitial lung disease (ILD) (N = 15), obesity (N = 15) and healthy controls (N = 16) were included. Compressed expiratory flow-volume curves (at mouth) and corresponding compression-free curves (thoracic) were recorded. Peak flow (PEF) and maximal flows at 75%, 50% and 25% of remaining forced vital capacity (MEF75, MEF50 and MEF25) were derived from both recordings. Their respective difference was assessed as an indicator of gas compression. Results In all groups, significant differences between thoracic and mouth flows were found at MEF50 (p < 0.01). In controls, a significant difference was also measured at MEF75 (p <0.005), in emphysema subjects, at PEF and MEF75 (p < 0.05, p < 0.005) and in obese subjects at MEF75 (p <0.005) and MEF25 (p < 0.01). ILD patients showed the lowest difference between thoracic and mouth flows at MEF75 relative to controls and emphysema patients (p < 0.005, p < 0.001). Obese subjects did not differ from controls, however, the difference between thoracic and mouth flows was significantly higher than in patients with emphysema at MEF50 (p < 0.001) and MEF25 (p < 0.005). Conclusions Alveolar gas compression distorts the forced expiratory flow volume curve in all studied groups at the middle fraction of forced expiratory flow. Consequently, mouth flows are underestimated and the reduction of flow measured at 75% and 50% of vital capacity is often considerable. However, gas compression profiles in stiff lungs, in patients with decreased elastic recoil in emphysema and in obesity differ; the difference between thoracic and mouth flows in forced expiration was minimal in ILD at the first part of forced expiration and was higher in obesity than in emphysema at the middle and last parts of forced expiration.